A Cross-sectional Study of Correlation Between Andropause and Anxiety Disorders Among Police Officers in Bali - Aprilio, Sendi; Pramesemara, I Gusti Ngurah; Negara, I Made Oka (Indonesian Andrology and Biomedical Journal, 2024)
Background: Andropause is a clinical and biochemical syndrome associated with increasing age characterized by a decreased testosterone level. Anxiety disorders are mental disorders that differ from normal feelings of nervousness or anxiousness and involve excessive fear or anxiety. Police officers has a high risk of experiencing andropause and anxiety disorders because of the andropause. Objective: This research aims to determine the correlation between andropause and anxiety disorders in Bali police officers. Methods: This research was carried out with a cross-sectional analytic design. Andropause was measured using an ADAM questionnaire. Anxiety disorder was measured using a BAI questionnaire. The sample for this research was male police officers aged between 35-58 years who worked at the Ditreskrimsus Polda Bali. The sample was determined using a purposive sampling technique. The sample for this research consisted of 50 people. Results: The results showed that 60% of samples were positive for andropause and 62% of samples were positive for anxiety disorders. There are 52% sample that tested positive for both andropause and anxiety. There is a significant correlation between andropause and anxiety disorders with p value <0.001. Calculated Odds Ratio (OR 95% CI) between andropause and anxiety disorders was 19.5 (4.527-83.992). Police officers that experiencing andropause have a 19.5 times higher risk of experiencing anxiety disorders compared to police officers that not experiencing andropause. Conclusion: There is a significant correlation between andropause and the occurrence of anxiety in police officers in Bali.